The economics of innovation, new technologies and structural change - Antonelli, Cristiano (Studies in global competition., 2003)
The ongoing process of revising and rethinking the foundations of economic theory leads to great complexities and contradictions at the heart of economics. 'Economics of innovation' provides a fertile challenge to standard economics, and one that can help it overcome its many criticisms. This authoritative book from Cristiano Antonelli provides a systematic account of recent advances in the economics of innovation. By integrating this account with the economics of technological change, this exceptional book elaborates an understanding of the effects of the introduction of new technolo.